Workplace eco-anxiety: a scoping review of what we know and how to mitigate the consequences - Ayassamy, Prisca; Francoeur, Virginie; Paillé, Pascal (Frontiers in Sustainability, 2024)
Purpose: Eco-anxiety can affect individuals' environmental engagement conditions. People spend approximately 35 hours or more per week in a workplace environment. It is worth considering whether workplace initiatives exist to deal with eco-anxiety. Little research has been carried out on workplace-related eco-anxiety and no studies have been conducted on how to respond to this health issue within the workplace specifically. To address this issue, we explored eco-anxiety in a workplace context in the literature and developed a model of change to better respond to employees' eco-anxiety. Methodology: First, a scoping review was conducted to investigate workplace eco-anxiety. Second, an analysis was performed in which Lewin's theory of change was used to propose changes in the workplace designed to better respond to eco-anxiety. Findings: Lewin's three stages can guide action to reduce eco-anxiety in the workplace.Step 1 (unfreeze) involves becoming aware of the eco-anxiety problem within the organization, step two (change) consists of finding alternatives in the built environment such as green spaces and pro-environmental behaviour through circular economy practices, and step 3 (refreeze) involves stabilizing this change. Originality: Our study is among the few to explore eco-anxiety in the workplace specifically and, to our knowledge the first, to propose an intervention model for management and employees. Lewin's three stages can guide action to reduce eco-anxiety in the workplace.